2016
DOI: 10.1016/j.jcf.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance in young patients with cystic fibrosis: Validation of a specific equation and clinical relevance

Abstract: BIA, based on a CF-specific equation, is a reliable method for BC assessment and allows the identification of patients at risk of nutritional degradation and bad respiratory prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 47 publications
5
33
0
1
Order By: Relevance
“…DXA relies on principles of x‐ray absorptiometry similar to CT but is associated with an extremely low radiation dose; as a result, DXA is able to be used in a much wider range of clinical populations 47 51 . In fact, due to the safety and availability of DXA scans, they are often used to validate various other body composition–estimating devices and equations, including CT 31 , 52 55 …”
Section: Dxamentioning
confidence: 99%
“…DXA relies on principles of x‐ray absorptiometry similar to CT but is associated with an extremely low radiation dose; as a result, DXA is able to be used in a much wider range of clinical populations 47 51 . In fact, due to the safety and availability of DXA scans, they are often used to validate various other body composition–estimating devices and equations, including CT 31 , 52 55 …”
Section: Dxamentioning
confidence: 99%
“…The authors reported a very good accordance of both techniques and demonstrated that patients with reduced FFM, consisting of the body's water, bone, organs and muscle content, showed worse pulmonary function. 18 In our study using serial BIAs, the parameter ECM/ BCM ratio was the most accurate predictor of pulmonary function and superior to FFM. BCM consists of the whole-body cell mass, such as metabolically active organs and particularly muscles, whereas ECM includes the connective tissues such as collagen, elastin, skin, chords and bones, as well as interstitial water.…”
Section: Discussionmentioning
confidence: 55%
“…17 Recently, Charatsi et al evaluated BIA in comparison to DXA in a cross-sectional study of 54 paediatric CF patients and reported a very good accordance of both techniques, thus demonstrating that BIA can be reliably used in CF patients. 18 Additionally, patients with reduced FFM values showed worse pulmonary function, a finding that merits further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies proposed the use of population‐specific BIA equations to improve the accuracy of the measurements . Charatsi et al validated the only CF‐specific equation for BIA using DXA as a reference method …”
Section: Resultsmentioning
confidence: 99%
“…Studies documented a significant association between a decrease in FFM and impaired pulmonary function or poor respiratory muscle strength in patients with CF . Therefore, in recent years, there has been a growing research interest in comparing the accuracy of different BC methods in patients with CF and in the investigation of the relationship between BC and health outcomes …”
Section: Introductionmentioning
confidence: 99%